Controle por modos deslizantes global aplicado ao posicionamento dinâmico de veículos subaquáticos autônomos - Chiella, Antonio Carlos Bana (2015)
In recent years, there has been a growth in the interest of industry and the scientific community for autonomous platforms, among these so-called AUVs (Autonomous Underwater Vehicle). Part of this interest is due to technological progress, with improved electronics and the reduction of its cost. Another part is due to application of this equipment in a variety of tasks such as inspection and maintenance of underwater structures in marine environment (oil and gas platforms) and recently inspection of hydroelectric plants. These robots allow the removal the operator of the region conducting task, reducing the risks in carrying it. In an attempt to make these fully autonomous platforms, reducing the efforts of the operator, challenges related to its control position emerge. In this work, the AUVs positioning control problem is addressed. The kinematic and dynamic models for the 6 degrees of freedom of these robots, as well as the modeling of the actuators and the external disturbances are presented. Characteristics of the mathematical model are used in the controller design, titled CMDG (Global Sliding Mode Control). The proposed controller is based on the sliding mode control, and its sliding surface was modified so as to delete the so called reaching phase. Numerical simulations show the good performance of the proposed controller when subjected to disturbances such as current, non-zero buoyancy and initial position errors.